Contribution of different nitrogen sources and origins to seed N during soybean seed filling: impact of water deficit and N availability - Ergo, Verónica Vanesa; Salvagiotti, Fernando; Carrera, Constanza Soledad (Embrapa Soja, 2025)
Poster y resumen